Pengaruh Pupuk Organik Plus terhadap Pertumbuhan Tanaman Tomat di Kabupaten Merauke - Nurhening Yuni Ekowati; Rosmala Widijastuti; Mani Yusuf; Adrianus Adrianus; Mariana Lusia Resubun; Jefri Sembiring; Johana Anike Mendes; Abdul Rizal (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Tomatoes are a horticultural commodity that is widely consumed by the public, so they need to be increased using organic fertilizer plus Trichoderma. This research aims to determine the effect of organic fertilizer plus on increasing the growth and production of tomato plants. This study used a randomized block design with treatments namely no organic fertilizer plus (A0), organic fertilizer plus 3 t.ha-1 (A1), 6 t.ha-1 (A2), 9 t.ha-1 (A3), 12 t.ha-1 (A4), and 15 t.ha-1 (A5). The variables observed were plant height, number of leaves, number of branches, number of flowers forming fruit, number of flowers, number of fruit, fruit weight, fruit diameter and productivity. The observational data is analyzed for variance and data that shows a real effect will be further tested using Duncan's Multiple Range Test. The results of the study showed that organic fertilizer plus treatment had an effect on the growth of tomato plants. The highest variables of plant height, number of leaves, stem diameter and number of branches were obtained in the organic fertilizer plus 15 t.ha-1 (P5) treatment which was not significantly different from the 12 t.ha-1 (P4), 9 t.ha-1 (P3), 6 t.ha-1 (P2), 3 t.ha-1 (P1), but significantly different from the treatment without organic fertilizer plus (P0).